A Rare Cause of Pacemaker Failure: Interatrial Block. Issue 5 (20th January 2013) - Demircan, Sabri; Yuksel, Serkan; Gulel, Okan
<x xml:space="preserve">Abstract</x> Pacemaker and implantable cardioverter defibrillators (ICD) systems are useful in detection and differentiation of many symptomatic and asymptomatic arrhythmias. In this report, we described a rare condition that caused by failure in detection of a clinical tachyarrhythmia by a dual chamber pacemaker that implanted because of intermittent atrioventricular (AV) block and sinus node disease in a 46‐year‐old patient. In our case, bidirectional interatrial block was demonstrated; and the symptoms associated with high ventricular rate caused by left atrial tachyarrhythmias relieved after AV node ablation.